Aktivitas Antibiotik terhadap Biofilm Staphylococcus aureus Isolat Preputium Sapi Aceh - Dewi, Maryulia; Darmawi, Darmawi; Nurliana, Nurliana; Karmil, T. Fadrial; Helmi, T. Zahrial; Fakhrurrazi, Fakhrurrazi; Erina, Erina; Abrar, Mahdi; AK, M. Daud; Admi, Masda (Jurnal Sain Veteriner, 2020)
Biofilm is one of parameters for determining pathogenic pathways of a bacterium. Bacterial virulence activities can be attenuated by antibiotics with inhibiting biofilm. The aim of this study was to examine the characteristics and activities of antibiotics against the biofilm of Stapylococcus aureus isolate which taken from Aceh cattle prepuce. The study was exploratory and experimental, using a Completely Randomized Design (RAL) factorial pattern using three types of antibiotics, three concentrations and replications. Antibiotics were tetracycline, oxytetracycline and phosphomycin with concentrations of 10%, 20% and 30% (mg/mL), respectively. Therefore, the aim of this study was to examine the characteristics and activities of antibiotics to the biofilm of Stapylococcus aureus from Aceh cattle prepuce isolate. U-bottom polystyrene 96 wells microplate and Nutrient Broth (NB) medium was used to biofilm bacterial while biofilm was stained on crystals violet 1%. Optical Density (OD) of biofilm were Î» 595 nm. Data were analyzed by using Analysis of Variance (ANOVA). The results showed that the activity of Staphylococcus aureus was moderately positive, i.e 2,667cell/Î¼L. It showed that antibiotics and concetrations have significant effect (P<0.05) to inhibit biofilm staphylococcus aureus. In additioon, tetracycline 30% (mg / mL) has the best ability to inhibit biofilms from 52,18% to 1,262 cell/Î¼L. Based on that fact, it can be concluded that the virulence of Staphylococcus aureus was moderate positive to be false positive.